Cover Picture: Deactivation of Mcl‐1 by Dual‐Function Small‐Molecule Inhibitors Targeting the Bcl‐2 Homology 3 Domain and Facilitating Mcl‐1 Ubiquitination (Angew. Chem. Int. Ed. 46/2016). Issue 46 (18th October 2016) - Song, Ting; Wang, Ziqian; Ji, Fangling; Feng, Yingang; Fan, Yudan; Chai, Gaobo; Li, Xiangqian; Li, Zhiqiang; Zhang, Zhichao
Abstract : Promotion of Mcl‐1 protein binding to the ubiquitin ligase Mule to catalyze its ubiquitination could enhance an apoptotic signaling pathway in cancer cells. In their Communication onpage 14250 ff. Z. Zhang and co‐workers identify a compound that zips these two proteins together by driving a non‐helical QRN motif on Mc1‐1 to adopt a helical conformation.